Supported Literacy for Adolescents : Transforming Teaching and Content Learning for the Twenty-First Century - Morocco, Catherine Cobb; Aguilar, Cynthia Mata; Bershad, Carol J. (San Francisco, CA Jossey-Bass, 2008)
Supported Literacy for Adolescents, written by nationally recognized experts, introduces an innovative and field-tested instructional framework for preparing secondary students to succeed academically in a fast-changing and globally networked world. Filled with examples from science, history, literature, and special education classrooms, the book shows how teachers can enable diverse students, including under-performers, to develop critical thinking and other essential competencies along with the "multi-literacy" tools needed to engage in twenty-first century content learning.
Include Appendices, References and Index.
Transforming Teaching and Content Learning for the Twenty-First Century.
Keywords: Teenagers--Education -- United States -- Curriculum planning